The relationship between G1 (c.260 G>A) and G4 (c.721 G>A) polymorphisms in the GDF9 gene and the litter size of sheep: A meta-analysis study (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The results of G1 and G4 polymorphisms as litter-size (LS) markers of ewes remain contradictory. The aim was to evaluate the impact of G1 (c.260 G>A) and G4 (c.721 G>A) polymorphisms on the LS of sheep by synthesizing data from multiple previous studies. Methods: Data were extracted from 14 eligible articles. The genotypes of G1 and G4 polymorphisms were homozygous wild-type (WW), heterozygous (WM), and homozygous mutanttype (MM). The standardized mean difference (SMD) method using random effect models was employed to determine the effect size of G1 and G4 polymorphisms on LS under dominant, recessive, additive, and co-dominant genetic models. Heterogeneity was analyzed with the I2 statistic index. Publication bias was depicted with funnel plots and tested by Egger’s and Begg’s tests. Results: The study showed that the correlation between G1 polymorphism and LS in sheep was not significant (p > 0.05) under all genetic models. The influence of G4 polymorphism on the LS of sheep was found significantly (p < 0.05) under dominant [SMD = 0.28, I2 = 0% (no heterogeneity)] and co-dominant [SMD = −0.14, I2 = 36% (moderate heterogeneity)] genetic models. The WM genotype of G4 polymorphism increased LS, while the MM genotype reduced LS in sheep. Publication bias among G1 and G4 polymorphism studies was absent in all genetic models. Conclusion: Thus, the study revealed that G4 polymorphism could be a potential genetic marker for LS in ewes. On the contrary, G1 polymorphism has no association with the LS of ewes.J. Adv. Vet. Anim. Res., 10(4): 599–607, December 2023http://doi.org/10.5455/javar.2023.j715